Collection of book manuscripts in a research library: problems of terminology - E. Y. Andreeva (Библиосфера)
The comparative analysis of terms used in professional literature is given. The introduction of the term «collection of book relics» for collections consisting totally of book relics (e.g. collection of manuscripts) is grounded.